ANATOMI DAN GAMBARAN ULTRASOUND ORGAN REPRODUKSI SELAMA SIKLUS ESTRUS PADA KUDA GAYO BETINA (Anatomy and Ultrasound Imaging of Reproductive Organs of Gayo Mares During Estrous Cycle) - Juli Melia; Muhammad Agil; Iman Supriatna; Amrozi Amrozi (Universitas Syiah Kuala, 2016)
The present study examines anatomy of Gayo mare reproductive organs. This study used three sample of Gayo mare reproductive organs (n= 3) for observation of morphology and morphometric of the mare reproductive organs. The ovarium was fixed in 4% paraformaldehyde solution then followed by histological method and stained using hematoxylin and eosin (HE) and Masson’s trichome (MT). Three mares were observed for diameter and changes overview of uterus during estrous cycle in real time using ultrasound. The results showed that, in general, the anatomy of Gayo mare’s reproductive organs was similar to other mares, but smaller in morphometry. The total length of the Gayo mare’s reproductive tract from labia to apex cornua was 48.00±1.00 cm. Weight of Gayo mare’s left ovary was 19.07±7.70 g and the right was 24.43±0.83 g. Histologically, there was no difference between Gayo mare’s structure and other mares. In cortex uteri there were some follicles surrounded by capillary, various development stages of follicles, healthy follicles, atretic follicle, and corpus albican; while in medulla there were a lot of connective tissues. Ultrasound of the uterus showed the change in diameter during estrous cycle with the largest diameter of corpus uteri was 4.43±0.10 cm in horses with estrous cycle of 21 days and 6.30±0.93 cm in horses with 24 days estrous cycle. In conclusion, the morphometry of Gayo mare reproductive organs are smaller than the other horses and there are differences in diameter of the uterus during the estrous cycle due to the changes of endometrium thickness.